PH-Control as a way to fine-tune the Cu/Cu2O ratio in radiation induced synthesis of Cu2O particles. Issue 45 (31st October 2018) - Li, Zhuofeng; Soroka, Inna L.; Min, Fanyi; Jonsson, Mats
Abstract : During the γ-radiation induced synthesis, composition and morphology of Cu–Cu2 O precipitate can be tuned by varying the aqueous CuSO4 solution pH in the narrow range from 3.75 to 4.40. Abstract : In this work we have optimized the γ-radiation induced synthesis of Cu–Cu2 O particles from aqueous CuSO4 solution by investigating the effect of pH. The obtained precipitate was analyzed by XRD and SEM techniques. The results indicated that at solution pH lower than 3.75, quasi-spherical Cu agglomerates can be formed while at pH higher than 4.40 only octahedron-shaped Cu2 O particles are produced. At solution pH in the range from 3.75 to 4.40, a Cu–Cu2 O mixture is produced. It was found that the relative amount of Cu2 O in the Cu–Cu2 O precipitate increases with pH in the studied range. The influence of solution pH on the Cu/Cu2 O ratios in the product can be explained on the basis of pH-dependent competition kinetics between the reactions leading to either Cu or Cu2 O formation. As a consequence, the composition and morphology of the Cu–Cu2 O precipitate can be tuned by controlling pH of the aqueous CuSO4 solution during the γ-radiation induced synthesis.